Smart Home Controlling System - Mahyuzie Jenal; Athira Nabilla Omar; Muhammad Azizi Aswad Hisham; Wan Najmi Wan Mohd Noh; Zul Adib Izzuddin Razali (Journal of Electronic Voltage and Application, 2022)
To minimize the need for human involvement, increased security and improved energy efficiency, a smart home control system can be integrated into current household appliances. The main objective of this project is to develop a home automation system as technology is advancing, therefore houses are also getting smarter. The proposed prototype of home automation in this study allows users to turn on or off any household equipment remotely via the Internet of Things (IoT). This paper presents a low cost and flexible home control and monitoring system using microcontroller, with Arduino Uno board connectivity for accessing and controlling devices and appliances remotely using BTDisplay app. All the basic appliances at home can be controlled by user from mobile device. The user will also be notified in any change if it goes beyond their given range. All the hardware, software and test fields design are discussed in this paper.